E-WoM Engagement and Purchase Intention on Social Commerce Specialized in Beauty Products: A Perspective from Young Female Consumers - Nono Wibisono; Widi Senalasari; Martin Elliott White; Agustinus Februadi (Politeknik Negeri Bandung, 2023)
This study intends to analyze the impact of e-WoM engagement on social commerce applications of beauty products on customer purchase intention. The Theory of Reasoned Action (TRA), Technology Acceptance Model (TAM), Elaboration Likelihood Model (ELM), and Social Support Theory were employed to investigate the effect of e-WOM engagement on purchase intention. Data were collected from 356 social commerce users in Indonesia, and PLS-SEM was used to analyze the relationship between variables. This study discovered that e-WoM engagement positively affects purchase intention. All the TAM constructs, consisting of innovativeness and social support, also have a positive impact on e-WoM engagement and purchase intention. However, information characteristics have no significant impact on e-WoM engagement. Business players of beauty products and managers of online businesses should pay attention to factors that shape customers’ attitudes to engage in e-WoM in order to stimulate positive e-WoM engagement. This study proposes a new model for research in the field of social commerce and becomes the first research concentrating on social commerce specializing in beauty products.